Respuesta :

Tucon
   
[tex]\displaystyle \\ 2x(x-1) = 3 \\ 2x^2 - 2x =3 \\ 2x^2 - 2x -3=0 \\ \\ x_{12} = \frac{-b \pm \sqrt{b^2-4ac} }{2a} =\frac{2 \pm \sqrt{4+24} }{4} = \\ \\ =\frac{2 \pm \sqrt{28} }{4} =\frac{2 \pm 2\sqrt{7} }{4} = \frac{1 \pm \sqrt{7} }{2} \\ \\ \boxed{x_1 = \frac{1 + \sqrt{7} }{2} } \\ \\ \boxed{x_2= \frac{1 - \sqrt{7} }{2} } [/tex]



Answer:

The distributive property says that:

[tex]a \cdot(b+c) =\acdot b+ a\cdot c[/tex]

Given the equation:

[tex]2x(x-1) =3[/tex]

Apply the distributive property:

[tex]2x^2-2x=3[/tex]

Subtract 3 from both sides we get;

[tex]2x^2-2x-3=0[/tex]           ....[1]

For the quadratic equation [tex]ax^2+bx+c =0[/tex] where a, b and c are coefficient then the solution is given by:

[tex]x_{1, 2} = \frac{-b \pm\sqrt{b^2-4ac}}{2a}[/tex]

On comparing general equation with the equation [1] we have;

a = 2 b = -2 and c= -3

then;

[tex]x_{1, 2} = \frac{-(-2) \pm\sqrt{(-2)^2-4(2)(-3)}}{2(2)}[/tex]

Simplify:

[tex]x_{1, 2} = \frac{2 \pm\sqrt{4+24}}{4}[/tex]

[tex]x_{1, 2} = \frac{2 \pm\sqrt{28}}{4}[/tex]

or

[tex]x_{1, 2} = \frac{2 \pm 2\sqrt{7}}{4} = \frac{1\pm \sqrt{7} }{2}[/tex]

⇒ [tex]x_{1} = \frac{1 +\sqrt{7}}{2}[/tex] and  [tex]x_{2} = \frac{1 -\sqrt{7}}{2}[/tex]

Therefore, the solution for the given equation are:

[tex]x_{1} = \frac{1 +\sqrt{7}}{2}[/tex] and  [tex]x_{2} = \frac{1 -\sqrt{7}}{2}[/tex]